Population dynamics of killer whales (Orcinus orca) in the Crozet Archipelago, southern Indian Ocean: a mark-recapture study from 1977 to 2002 - Poncelet , Eric; Barbraud , Christophe; Guinet , Christophe (J. Cetacean Res. Manage., 2023)
Population size and annual survival probabilities for the killer whales (Orcinus orca) inhabiting the inshore waters of Possession Island, Crozet Archipelago, southern Indian Ocean, were estimated through mark-recapture modelling. Capture histories were generated from a set of photographs taken under a photo-identification protocol and a set of photographs taken opportunistically, between 1964 and 2002. Photographs were selected according to their intrinsic quality and the degree of natural marking of individuals. Under those conditions, only well-marked individuals were considered as ‘marked’ from a capture-recapture perspective. The purpose of this double selection was to minimise identification errors and reduce the heterogeneity of capture probabilities. Abundance estimates were derived from the Mth sequential model for closed populations and adjusted for the proportion of well-marked individuals in the study population and for the number of photo-identified individuals. Under this framework, estimates of 98 (95% CI 70-156) individuals in 1988-89, and 37 (95% CI 32-62) individuals in 1998-2000 are proposed. After a weighted model averaging, the Cormack-Jolly-Seber models with the strongest support from the data produced low survival probability estimates, decreasing from 0.935 (95% CI 0.817-0.979) to 0.895 (95% CI 0.746-0.961) for males, and from 0.942 (95% CI 0.844-0.980) to 0.901 (95% CI 0.742-0.966) for females over the period 1977-2002. A Jolly-Seber model was used as a ‘second opinion’ model. It confirmed the worrying status of the population with a constant survival probability estimated at 0.89 (95% CI 0.84-0.93) and a constant rate of increase (applying to the well-marked fraction of the population) estimated at 0.94 (95% CI 0.90-0.99) for the period 1987-2000. This rate of increase is consistent with the abundance estimates presented here. Possible violations of the underlying model assumptions were investigated and it was concluded that the abundance estimates for the period 1988-89 and the CJS survival estimates should be the most reliable results. It is feared that the killer whales around Possession Island are in sharp decline, as may be true for the whole Crozet Archipelago. The effect of low prey stocks and lethal interactions with fisheries as the most likely causes of this decline are discussed.